La cultura tributaria desde la informalidad de los comerciantes de la Bahía de Guayaquil - Ordóñez Vivero, Rosa Elena (2014)
The current incidence of the tax culture in Ecuador is perceived in the formal and informal economic environment as it is conceived in the democratic values. Hence, the need to assess cognitively and technically the effectiveness of tax collection from the informal perspective of the traders at La Bahia in Guayaquil. Different governments have delved into the recovery, updating and usage of ideal data base related to the commercial activities and reliable income of the informal sellers to determine the economic variables that reflect the authenticity of the micro and macroeconomic results of the Ecuadorian reality, and that study area is a point of reference in Guayaquil. Research from the academy should aim at studying, analyzing and presenting results to help tax administration improve the trading conditions of tax payers, to encourage them to file taxes within deadlines and with the corresponding knowledge on how to update, how to declare so they can contribute through their active participation to the national development and to the progress towards the Ecuadorian plan of good living.